Microwave-Assisted Synthesis of Corn Husk-Based Hydrogels Grafted with Acrylamide - Ginanjar Penata Aji; Mahira Noor Syevarani Arifandi; Sperisa Distantina; Mujtahid Kaavessina (ALCHEMY Jurnal Penelitian Kimia, 2024)
Corn husk waste contains cellulose, which has the potential as a raw material for hydrogel preparation. Hydrogels can be applied as water purification, diapers, and superabsorbents. This study aimed to synthesize hydrogel from corn husk cellulose grafted with acrylamide monomer using a microwave-assisted grafting method. Potassium peroxodisulfate (PPD) was used as an initiator, and the effects of acrylamide and PPD on hydrogel swelling capacity were investigated. The process involved drying and crushing corn husks into powder, then mixing the powder with acrylamide and PPD for microwave grafting to form a polymer, which was then ground into powder. The grafted polymer was combined with carrageenan to create bead gels soaked in distilled water and urea to measure swelling capacity. Results showed that swelling capacity increased with more acrylamide and decreased with more PPD. The highest swelling capacity reached 1016.16% in water and 961.6% in urea. FTIR analysis confirmed the successful grafting of acrylamide onto corn husk cellulose by detecting changes in the infrared spectrum. Based on FTIR and swelling capacity data, it was concluded that the grafting process was completed using the microwave method with PPD as the initiator.